Rasulullah dan Peradaban Islam Madinah - Lukitarina (TABYIN: JURNAL PENDIDIKAN ISLAM, 2020)
Among one of the negatives characteristic of the Arabs before the arrival of Islam were the exaggerated taasub of tribes and their descendants. The nature of taasub found in the principle of those who hold firm tribalism as well as tribal primordial. An attitude that assumes that their tribe or tribe is the most superior, noble than the other tribes. This condition becomes a challenge for the Prophet Muhammad to convey his treatise and unite the Arabs. Because uniting them under one banner of leadership is not easy. It could be seen in the period of Mecca, where during the 13 years of the Prophet preached, has not given any significant results, let alone form a civilized state order. Meanwhile, in Medina, the Aus and Khazraj tribes as the two leading tribes are also hostile to each other. This was seen before the Prophet’s Hijrah. But the condition changed after the Prophet emigrated. Where he as a messenger of God’s vision and mission, able to set a strategy in eliminating the concept of tribal primordial among them. So he could make them become brothers of faith and belief. In fact, he was able to form the Islamic State of Madinah in the middle of the tribal primordial and unite them in one command even though the people are coming from the different race, ethnicity and religion. In the end, there creates a sense of mutual help and tolerance that is so high among them and actualized a country full of peace and civilization.